Validity and Reliability of an Electronic Contact Mat for Drop Jump Assessment in Physically Active Adults - Florian Tenelsen; Dennis Brueckner; Thomas Muehlbauer; Marco Hagen (MDPI AG, 2019)
The aim of the present study was to investigate the concurrent validity and the test–retest reliability of an electronic contact mat for drop jump assessment in physically active adults. Seventy-nine young, physically active adults participated in the validity study, and 49 subjects were recruited for the reliability study. The motor task required subjects to perform two-legged drop jumps using drop heights of 24, 43, and 62 cm as well as one-legged drop jumps with the left and right leg using a drop height of 24 cm. Ground contact times were simultaneously quantified with an electronic contact mat, a force plate (i.e., gold standard), and a light-barrier system (another criterion device). Concurrent validity was assessed using intraclass correlation coefficient (ICC), systematic bias, limits of agreement, and linear regression analysis. Test–retest reliability (one week apart) was determined by calculating the ICC, the standard error of measurement (SEM), the coefficient of variation (CV), and Lin´s concordance correlation coefficient (рc). Further, we determined the minimal detectable change (MDC95%). Irrespective of drop height and jump condition, good agreements between testing devices (ICC ≥ 0.95) were shown. Compared to the force plate (−0.6 to 3.1 ms) but not to the light-barrier system (31.4 to 41.7 ms), the contact mat showed low systematic bias values. In terms of test–retest reliability, our analyses showed that the measuring devices are in agreement (ICC: 0.70–0.92; SEM: 8.5–18.4 ms; CV: 3.6–6.4%). Depending on the measurement device, drop height, and jump condition, a MDC95% value ranging from 23.6 to 50.9 ms represents the minimum amount of change needed to identify practical relevant effects in repeated measurements of drop jump performance. Our findings indicate that the electronic contact mat is a valid and reliable testing device for drop jump assessment from different drop heights in young physically active adults.